Tensile properties of plant fibre‐polymer composites in fire. (13th June 2017) - Bhat, T.; Kandare, E.; Gibson, A. G.; Di Modica, P.; Mouritz, A. P.
Summary: The structural performance of polymer composites reinforced with plant fibres when exposed to fire was experimentally evaluated and compared against an E‐glass fibre laminate. Fire testing under combined one‐sided radiant heating and static tensile loading revealed that flax, jute, or hemp fibre composites experience more rapid thermal softening and fail within much shorter times than the fibreglass laminate, which is indicative of vastly inferior structural performance in fire. The plant fibre composites soften and fail before the onset of thermal decomposition of the plant fibres and polymer matrix, whereas the E‐glass fibres provide the composite with superior tensile properties to higher temperatures and higher applied tensile stresses. The tensile performance of the three types of plant fibre composites in fire was not identical. When exposed to the same radiant heat flux, the flax fibre composite could withstand higher tensile stresses for longer times than the hemp and jute laminates, which showed similar performance.